Ekspor Sampah Uni Eropa ke Indonesia sebagai Bentuk Eco-Imperialism - Khairunnisa, Meyfitha Dea (Jurnal Transformasi Global, 2021)
Environmental policy has become an important aspect of reviewing international relations environmental issues. The European Union is a regional institution that has been very active in international environmental cooperation. However, at the same time, the European Union is one of the largest waste exporters to countries in Asia, including Indonesia. Waste export is a free trade mechanism that allows developed countries to send waste to developing countries to be processed as industry materials. This then becomes contradictory to the commitment of the European Union in promoting environmentally friendly policies, and policies for the export of waste are considered as a form of ecoimperialism. This article discusses how the waste export policy by the European Union has become a form of ecological colonization for Indonesia as a waste recipient. Keywords: Waste Export; Eco-Imperialism; Environmental Policy